Studi Keterkaitan Kapabilitas Inovasi dan Kinerja Inovasi UKM Alas Kaki di Mojokerto - Benny Lianto; Esti Dwi Rinawiyanti; Fendy Soeharsono (Asian Journal of Innovation and Entrepreneurship, 2015)
This paper presents the results of a study on the relationship of innovation capabilities and performance of SMEs related to innovation activity (innovation performance) by taking into account the characteristics of the company in footwear Small and Medium Enterprises (SMEs) in Mojokerto. Innovation capabilities of SMEs was measured using the concept of Technological Innovation Capabiliities (TIC) with 7 (seven) dimensions of capability, ie learning capability, R&D capability, manufacturing capability, marketing capability, resources allocatioin capability, organizational capability, and strategic planning capabilities; while the innovation performance of SMEs related activity was measured using the concept of Technological innovation performnace (TIP) with 4 (four) dimensions of performance, namely sales performance, innovation performance, product performance, and sales growth performance. Characteristics of SMEs were described through 4 main variables, namely the scale of the business, the company age, the type of product, and the location of the business location.This study was conducted on 82 Footwear SMEs in Mojokerto, which is in Sooko (village of Wringin Rejo, Japan, Karang Kedawang, Jampirogo and Sambiroto), Trowulan District (Pakis village), Pungging District (Tunggal Pager village) and Puri District. The process of data collection was done by interviews and questionnaires to the owners and managers of SMEs. The sampling method used was non-probability purposive sampling and the population used was footwear SMEs in Mojokerto. The data analysis technique used was structural equation modeling (SEM) based on the Component or Variance - PLS program operated through SmartPLS version 2.0.The results of study showed that, manufacturing capability was predicted to affect product performance and organizational capability was estimated to give an impact on the innovation capability, sales growth and sales performance. Some dimensions of innovation capabilities that have absolutely no influence on the performance of SMEs were learning capability, R&D capability, resources allocation capability, marketing capability, and strategic capability. Results of Manova analysis stated that the characteristics of SMEs (the location of SMEs) gave effect to both the innovation capabilities and the innovation performance of SMEs. Keywords: kapabilitas inovasi, kinerja inovasi, UKM alas kaki, Mojokerto